PERLINDUNGAN HUKUM TERHADAP KREDITUR DALAM EKSEKUSI OBYEK HAK TANGGUNGAN BERDASARKAN PARATE EKSEKUSI - , RONALD T. MANGALIK.SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to determine the protection against creditors in the execution object based parate executie mortgage. Another aim is to know the existence of the first mortgage holders and creditors in the form of legal protection against objects executie parate mortgage. This research is a normative legal research using qualitative analysis of judicial use of primary legal materials